Lloyd and Freeman's introduction to jurisprudence. - Byrne, Gavin (Gavin D.) (Sweet & Maxwell, 2025)
Widely regarded as the leading text in this field, covering the whole field of jurisprudence and justice, combining a vast array of extracts from the world's greatest jurists and thinkers with engaging commentary.